Improvement of PLA film ductility by plasticization with epoxidized karanja oil. (September 2020) - Garcia-Garcia, D.; Carbonell-Verdu, A.; Arrieta, M.P.; López-Martínez, J.; Samper, M.D.
Abstract: In this work, karanja oil has been epoxidized and further used as biobased plasticizer to improve some properties of poly (lactic acid) (PLA). The use of epoxidized karanja oil (EKO) has been studied because karanja oil is used in organic farming as an insecticide and generating an epoxidation of the oil can act as a PLA plasticizer. Melt extrusion was used to plasticize PLA with different EKO amounts in the 0–10 wt%. The formulations with EKO decrease the glass transition temperature as the EKO content increases and, in addition, generates an increase in elongation at break. Plasticizer saturation is observed by scanning electron microscopy (SEM) above 5% of EKO. PLA formulation with 5 wt% shows an optimal balance between the improvement of the fragility of the material, improving the elongation at breakage by 77%, using a relatively small concentration of plasticizer. Moreover, all materials were disintegrated under composting conditions at laboratory scale level. Highlights: Karanja oil has been seccessfully epoxidized and use as PLA plasticizer. Epoxidized karanja oil improved the ductility of PLA. Epoxidized karanja oil improved thermar stability of PLA. PLA with 5% EKO presents a balance between resistant and ductile properties. All formulations were fully disintegrated under composting.